2008
DOI: 10.1039/b812405a
|View full text |Cite
|
Sign up to set email alerts
|

Palladation of diimidazolium salts at the C4 position: access to remarkably electron-rich palladium(ii) centers

Abstract: a Palladation of C2-protected diimidazolium salts with Pd(OAc) 2 afforded complexes comprising C4-bound N-heterocyclic dicarbene ligands. The reactivity of these complexes towards Lewis acids (AgBF 4 , AgOAc) and Brønsted acids (H 2 SO 4 , H 3 PO 4 , HOAc) revealed that abnormal C4 bonding of the carbenes markedly increases the nucleophilicity of the coordinated palladium center as compared to C2 bonding. Despite its formal +2 charge, the palladium center in these complexes is best described as a Lewis base. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
56
0
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 57 publications
(63 citation statements)
references
References 76 publications
4
56
0
3
Order By: Relevance
“…The latter two precursors have been used predominantly for C pyridinium -H bond activation, while Pd(OAc) 2 has been more widely applied, including C-H activation of imidazolium, pyridinium, and triazolium salts. The bond activation with Pd(OAc) 2 presumably involves the formation of an azolium palladate precursor (diimidazolium)[PdI 2 (OAc) 2 ] originating from coordination of the halide of the azolium salt to the palladium center [16]. Support for such a palladate formation has been obtained through NMR investigations and from the fact that palladation using azolium salts with noncoordinating PF 6 -or BF 4 -anions fail to undergo C-H bond activation.…”
Section: C-h Bond Activationmentioning
confidence: 95%
See 1 more Smart Citation
“…The latter two precursors have been used predominantly for C pyridinium -H bond activation, while Pd(OAc) 2 has been more widely applied, including C-H activation of imidazolium, pyridinium, and triazolium salts. The bond activation with Pd(OAc) 2 presumably involves the formation of an azolium palladate precursor (diimidazolium)[PdI 2 (OAc) 2 ] originating from coordination of the halide of the azolium salt to the palladium center [16]. Support for such a palladate formation has been obtained through NMR investigations and from the fact that palladation using azolium salts with noncoordinating PF 6 -or BF 4 -anions fail to undergo C-H bond activation.…”
Section: C-h Bond Activationmentioning
confidence: 95%
“…Experiments using the diimidazolium system 1 have indicated that the first Pd-C formation is irreversible (Scheme 1; Mes = mesityl) [16]. Unlike strong acids such as HCl, weaker acidic HOAc-which is the side product from acetate-mediated palladation of azolium salts-cannot cleave the Pd-C bond in intermediate C. The irreversibility of the bond forming process 7 together with the high yield of cyclopalladated dicarbene complex 2 point to an early preequilibrium that triggers the regioselectivity of C-H bond activation to the 'inner' carbon.…”
Section: C-h Bond Activationmentioning
confidence: 99%
“…119 It has been suggested that the efficient discrimination between the C4-H and C5-H for bond activation occurs through ion pairing of the diimidazolium dication with the -ate complex that forms upon coordination of the anions from the diimidazolium salt to the metal precursor (D, Scheme 7). 120 Alternatively, multiple anion-π interactions may be operational. 121 Such weak interactions provide a thermodynamic control that is principally related to that exerted by donor atom coordination to the metal precursor as discussed above (cf.…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, the normal analogues 28 are stable under identical conditions, even at elevated temperatures. 36 The former reactivity has been suggested to reflect an increased nucleophilicity of the palladium(II) center in 27, because of the stronger donor ability of the C4-bound carbene, compared to the 2-imidazolylidenes. Theoretical studies by Frenking and co-workers support this conclusion.…”
Section: C-h Bond Activation Of C2-substituted Imidazolium Saltsmentioning
confidence: 99%